Structural basis for substrate recognition mechanism of human SLC26A7 - Li, Xiaorong; Yang, Xiaoxu; Lu, Xiaoli; Lin, Bingqian; Zhang, Yuanyuan; Huang, Bangdong; Zhou, Yutong; Huang, Jing; Wu, Kun; Zhou, Qiang; Chi, Ximin (Nature communications, 2025)
Solute carrier family 26 (SLC26) mainly mediates transmembrane transport of various anion ions, including chloride and other halide ions, bicarbonate, oxalate, and sulfate. Many severe hereditary human diseases are correlated with SLC26 protein mutations. Here we report cryo-EM structures of human SLC26A7 in apo and iodide binding states. We identify non-canonical binding site for halide ions in SLC26A7. Molecular dynamics simulation and electrophysiological assay confirm the functional importance of key residues involved in iodide and chloride coordination. Together, our discovery marks a step towards an in-depth understanding of SLC26 family protein transport mechanisms. Solute carrier family 26 (SLC26) mediates transmembrane transport of negatively charged ions. Here, the authors report cryo-EM structures of human SLC26A7 in apo and iodide binding states, providing insight into the ion recognition mechanism of SLC26 family proteins.